2004
DOI: 10.1097/01.wnf.0000137862.67131.bf
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q 10 Improves Lactic Acidosis, Strokelike Episodes, and Epilepsy in a Patient With MELAS (Mitochondrial Myopathy, Encephalopathy, Lactic Acidosis, and Strokelike episodes)

Abstract: Mitochondrial encephalomyopathies encompass a group of disorders that have impaired oxidative metabolism in skeletal muscles and central nervous system. Many compounds have been used in clinical trials on mitochondrial diseases, but the outcomes have been variable. It remains controversial whether treatment of mitochondrial diseases with coenzyme Q 10 is effective. This paper describes a case of mitochondrial myopathy, encephalopathy, lactic acidosis, strokelike episodes, and exercise intolerance successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 25 publications
1
27
0
5
Order By: Relevance
“…Insgesamt konnten in den genannten Studien Spiegel erreicht werden, die den Elektronentransport der mitochondrialen Atmungskette von Parkinson-Patienten signifikant verbessert [34]. Zusätzlich konnten in kleineren Fallserien Patienten mit bekanntem hereditärem CoQ10-Defekt oder mitochondrialen Defekten klinische Verbesserungen mit diesen Dosierungen von CoQ10 erreicht werden [1,4,13,16,22]. Eine Behandlung mit 600 mg/Tag, einer Standardformulierung von CoQ10, über 3 Monate führte beispielsweise bei der Friedreich-Ataxie zu einem verbesserten bioenergetischen Status im Herzmuskel und in der Willkürmuskulatur [11].…”
Section: Pharmakokinetik Von Koenzym Q 10unclassified
See 2 more Smart Citations
“…Insgesamt konnten in den genannten Studien Spiegel erreicht werden, die den Elektronentransport der mitochondrialen Atmungskette von Parkinson-Patienten signifikant verbessert [34]. Zusätzlich konnten in kleineren Fallserien Patienten mit bekanntem hereditärem CoQ10-Defekt oder mitochondrialen Defekten klinische Verbesserungen mit diesen Dosierungen von CoQ10 erreicht werden [1,4,13,16,22]. Eine Behandlung mit 600 mg/Tag, einer Standardformulierung von CoQ10, über 3 Monate führte beispielsweise bei der Friedreich-Ataxie zu einem verbesserten bioenergetischen Status im Herzmuskel und in der Willkürmuskulatur [11].…”
Section: Pharmakokinetik Von Koenzym Q 10unclassified
“…Zusätzlich ist CoQ10 ein Antioxidans sowohl in Mitochondrien als auch Lipidzellmembranen [15]. Exogen zugeführtes CoQ10 ist entsprechend in der Lage, den Elektronentransport von Komplex I in normalem Gewebe zu erhöhen und verbessert die biochemischen und klinischen Parameter bei Patienten mit bekannten mitochondrialen Erkrankungen [1,4,13,22]. Neuere Studien zeigen, dass CoQ10 zusätzlich ein obligater Kofaktor bestimmter mitochondrialer Proteine, den so genannten "uncoupling proteins", ist [7,8].…”
unclassified
See 1 more Smart Citation
“…Numerous case reports and small, open-label studies describe mitochondrial diseases of varying severity that have responded to CoQ 10 supplementation, typically in dosages from 30 to 300 mg/ day [Gold et al, 1996;Berbel-Garcia et al, 2004]. A 3-month trial included 8 patients with mitochondrial encephalomyopathies supplemented with 160 mg CoQ 10 / day.…”
Section: Mitochondrial Disordersmentioning
confidence: 99%
“…Combination therapy of coenzyme Q10 with alpha lipoic acid appears to reduce serum lactate levels by targeting reactive oxygen species (free radicals), although normalization of these does not indicate disease remission. 69,70 Double-blind trials have not yet demonstrated any long-term benefit for coenzyme Q10. In contrast, several prospective studies have shown improved endothelial function and a possible preventive benefit for long-term L-arginine therapy.…”
Section: What Is Melas?mentioning
confidence: 99%